Gonadal development of striped catfish (Pangasianodon hypophthalmus) in climate-caused salinity intrusion (Asian Journal of Medical and Biological Research, 2024)
Salinity intrusion is one of the major climate-caused problems globally. The present work evaluated the impacts of salinity on the gonadal improvement in striped catfish (Pangasianodon hypophthalmus). The fingerlings of striped catfish (8.63 g) were cultured at three different salinity levels (0, 4, and 8 ppt) for two years. Gonadal development was assessed by gonadosomatic index (GSI) and histological analysis over six months at the end of two years of rearing from April to September. The gonad histological observations and the associated changes in GSI showed that the male and female striped catfish cultured in different salinity conditions could complete testicular and ovarian maturation at 4 and 8 ppt salinity by June and July, as they have grown at 0 ppt salinity. The current findings indicate that despite a slow rate of development, salinity up to 8 ppt showed a positive impact on the gonadal development of striped catfish.Asian J. Med. Biol. Res. 2024, 10(2), 89-98